ESTIMASI PENYIMPANAN KARBON EKOSISTEM LAMUN DI DESA SUKAJAYA, KABUPATEN PESAWARAN - anma hari kusuma; Eko Efendi; Amril Ma’ruf Siregar; Novi Susetyo Adi; Agustin Rustam; Nazolla Audia Laresty (Universitas Mataram, 2024)
Climate change is caused by an increase in the concentration of greenhouse gases, especially carbon dioxide (CO2) in the atmosphere since the industrial revolution. One of the ways to mitigate climate change is blue carbon. Blue carbon is the ability of coastal and marine ecosystems to absorb CO2 in the atmosphere through the process of photosynthesis and convert it into biomass and deposit it in sediment. Seagrass is one such blue carbon ecosystem. Seagrass is an ecosystem formed from higher plants that are able to adapt to saline environments by living completely submerged in the sea. This research was conducted with the aim of analyzing carbon stores in the seagrass ecosystem in Sukajaya Village. This research was conducted in Sukajaya Village, Pesawaran Regency, Lampung Province. The results of this research are that the composition of seagrass consists of Enhalus acoroides, Thallasia hemperichi and Halodule uninervis. Seagrass vegetation carbon stores are 31,94 gC/m2 while seagrass sediment carbon stores are 12,02 gC/m2. Keywords: Climate Change, Blue Carbon, Sea Grass, Sukajaya Village